Construction of a N, P doped 3D dendrite-free lithium metal anode by using silicon-containing lithium metal. Issue 35 (4th August 2022) - Zhang, Yuanxing; Wu, Borong; Mu, Daobin; Ma, Chengwei; Zhang, Xinyu; Wang, Yuanshen; Zhao, Zhiguang; Liu, Tao; Liu, Chengcai
Abstract : A 3D stable composite anode (DLi/LiSi x CA) prepared by using N-doped silicon-containing lithium metal on a polyaniline modified carbon cloth (PMCC) support was prepared, which exhibits excellent electrochemical performance in symmetrical cell and full cell batteries. Abstract : Lithium is thought to be an excellent anode material for next-generation Li metal batteries (LMBs). However, some problems with lithium anodes often lead to serious safety concerns and catastrophic failures due to the huge volume change, Li dendritic growth, and related side reactions. Therefore, in order to manufacture stable rechargeable batteries, the abovementioned serious problems must be effectively solved. In this paper, a three-dimensional N, P-doped silicon-containing lithium anode is designed and prepared by in situ metallurgy using low-cost Si3 N4 . The 3D stable composite anode (DLi/LiSi x CA) was prepared by adding a small amount of Si3 N4 to molten lithium to form N-doped silicon-containing lithium metal which was supported on a polyaniline modified carbon cloth (PMCC). The results show that the DLi/LiSi x CA not only has high Li affinity but can also effectively inhibit lithium nucleation and lithium dendritic growth, so as to maintain good structural stability in the process of Li plating/stripping. The new lithium metal anode based on doping and 3D carbon cloth shows good cycling stability and low polarizability in both symmetrical and full cells.